Validity and Reliability of the Persian Version of Internet Sex Screening Test in Iranian Medical Students. Issue 3 (2nd October 2019) - Shalbafan, Mohammadreza; Najarzadegan, Mohammadreza; Soraya, Shiva; Rashedi, Vahid; Najafian, Ruohollah; Ahmadkhaniha, Hamidreza; Seddigh, Ruohollah; Hassanzadeh, Morteza; Saeedi, Vahid; Kamalzadeh, Leila
Abstract: This study investigated the cultural adaptation, validity, and reliability of the Persian version of Internet Sex Screening Test (P-ISST). In this cross-sectional study, 97 medical students were included. Content and face validity of the questionnaire were established by experts. The item-level content validity index ranged from 0.83 to 1.0. Internal consistency for the P-ISST total score ( α = 0.923) was acceptable. Except for the "Online sexual spending" subscale, the Cronbach's alpha values for subscales fell between 0.7 and 0.9. This instrument can be used as an easily administered screening tool for assessment of online sexual activities in university students.